Sustainable Public Art Framework And Guidelines (SPAFG) for Melaka town areas / Azahar Harun ... [et al.] - Harun, Azahar; Abu Hassan, Sharmiza; Mohd Abdul Ghani, Khairunnisa; Pattanachotti, Ohm (Universiti Teknologi MARA, Perak, 2024)
Despite the meticulous endeavours of local municipal councils, public art initiatives within various town areas of Melaka exhibit a lack of novelty, resulting in their inability to establish an enduring impact. Previous studies have indicated that the present situation can be primarily ascribed to inadequate strategic foresight, ineffective decision-making processes, and a deficiency in artistic literacy. In order to address this matter, our research presents the Sustainable Public Art Framework and Guidelines (SPAFG), a holistic strategy aimed at improving urban embellishment and supporting the municipal councils of Melaka, particularly in the areas of public art planning, governance, and policy development. The SPAFG engages in the process of comparing and associating with various data sources throughout its developmental phases. These sources include the Sustainable Development Goals (SDG11, SDG15, and SDG17) as well as the Public Art framework that has been adopted by several city councils in western countries, and evaluations conducted by professionals specialising in sculptural art, landscape architecture, and art gallery management. The SPAFG, contains five unique themes, including Human and Environment, Creative Intervention, Culture and Heritage, Policy and Governance, and Economic Drivers and Motivation. The relevance and benefits SPAFG) initiative lie in its capacity to enhance awareness, facilitate education, and offer direction to town councils in making informed decisions regarding the implementation of public art within the urban spaces of Melaka. By adhering to the principles of the SPAFG framework, local authorities can effectively contribute to the achievement of sustainable development goals and facilitate the establishment of significant and influential public art initiatives.